2005
DOI: 10.1186/1471-2261-5-18
|View full text |Cite
|
Sign up to set email alerts
|

The BpTRU automatic blood pressure monitor compared to 24 hour ambulatory blood pressure monitoring in the assessment of blood pressure in patients with hypertension

Abstract: BackgroundIncreasing evidence suggests that ABPM more closely predicts target organ damage than does clinic measurement. Future guidelines may suggest ABPM as routine in the diagnosis and monitoring of hypertension. This would create difficulties as this test is expensive and often difficult to obtain. The purpose of this study is to determine the degree to which the BpTRU automatic blood pressure monitor predicts results on 24 hour ambulatory blood pressure monitoring (ABPM).MethodsA quantitative analysis com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
147
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 20 publications
8
147
1
2
Order By: Relevance
“…In the aforementioned study by Beckett and Godwin, 12 in 481 patients mean awake ambulatory BP (142/80 mm Hg) was similar to the mean of 5 readings taken with the fully automated BpTRU device (140/80 mm Hg) with the patients resting alone in a quiet examining room. Similar findings were noted in a report 9 from another one of our centers with the mean awake ambulatory BP in 309 patients (134/77 mm Hg) being similar to the mean of 5 automated office BP (AOBP) readings (132/75 mm Hg), once again, taken with the patients resting alone in a quiet examining room.…”
Section: Automated Bp Measurement In the Office Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aforementioned study by Beckett and Godwin, 12 in 481 patients mean awake ambulatory BP (142/80 mm Hg) was similar to the mean of 5 readings taken with the fully automated BpTRU device (140/80 mm Hg) with the patients resting alone in a quiet examining room. Similar findings were noted in a report 9 from another one of our centers with the mean awake ambulatory BP in 309 patients (134/77 mm Hg) being similar to the mean of 5 automated office BP (AOBP) readings (132/75 mm Hg), once again, taken with the patients resting alone in a quiet examining room.…”
Section: Automated Bp Measurement In the Office Settingmentioning
confidence: 99%
“…In the study of Beckett and Godwin, 12 the coefficient of correlation between the mean awake ambulatory systolic/diastolic BP and the family physician's routine BP was (rϭ0.15/rϭ0.32) compared to (rϭ0.57/rϭ0.61) for readings taken with the automated BpTRU device. Similarly, Myers et al 9 reported a higher correlation (rϭ0.62/rϭ0.72) between the mean awake ambulatory systolic/diastolic BP and the automatic office BP compared to the routine family physician readings (rϭ0.32/rϭ0.48).…”
Section: Automated Bp Measurement In the Office Settingmentioning
confidence: 99%
“…Pre-enrollment mean BP of 150/81 mmHg was reduced to 136/78 mmHg with AOBP and 141/80 mmHg with MOBP compared to the awake ABPM reading of 133/74 mmHg [27]. In comparison with MOBP in this evaluation and others, a significantly stronger BP correlation exists between mean AOBP and awake ABPM measurements [8,25,27].…”
Section: Automated Office Blood Pressure Monitoringmentioning
confidence: 72%
“…Importantly, AOBP monitoring does not appear to be affected by location [22,23] and has been studied in a variety of different practice settings, ranging from community-based pharmacies [24], primary care practice exam rooms [25], 24-hour ABPM units [8], and waiting rooms [26]. The ability to obtain valid AOBP readings in waiting rooms exemplifies that additional space or a private room is unnecessary to realize benefits from this device.…”
Section: Automated Office Blood Pressure Monitoringmentioning
confidence: 99%
“…En el levantamiento de Ontario, los promedios de la PA obtenidas con el aparato automático fueron menores cuando comparadas a las lecturas manuales 23 . Las lecturas automáticas, cuando no obtenidas de forma simultánea y realizadas sin la presencia del observador, pueden reflejar el verdadero status de la hipertensión en la población por minimizar el efecto de la bata blanca, ya que hay una gran proximidad entre las lecturas automáticas con el promedio de la PA ambulatoria diurna, medición estándar actual para evaluar el riesgo cardiovascular 29 .…”
Section: Pas (Oscilométrico)unclassified